Improving the Quality of Learning Through the Campus Program Teaching in SMK Negeri Seni and Budaya Raya Simalungun Regency - Asnewastri; Ginting, Andres M.; Hutauruk, Ahmad Fakhri; Hasugian, Jalatua H.; Chandra, Satria (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research discusses the implementation of the Teaching Campus Program in improving the quality of learning at the State Vocational School of Arts and Culture, Simalungun Regency. The research method used is qualitative descriptive with interview, observation, and documentation techniques. The results of the study show that this program contributes positively to improving students' literacy and numeracy through various activities such as learning assistance, library management, and technology adaptation. Teachers and students have responded positively to the program, especially in helping students who have difficulty reading and arithmetic. In conclusion, the Teaching Campus Program is able to improve the quality of learning and encourage students to play an active role in the equitable distribution of education.